“Nothing to Lose, Absolutely Everything to Gain”: Patient and Caregiver Expectations and Subjective Outcomes of Deep Brain Stimulation for Treatment-Resistant Depression - Thomson, Cassandra J.; Segrave, Rebecca A.; Fitzgerald, Paul B.; Richardson, Karyn E.; Racine, Eric; Carter, Adrian (Frontiers in Human Neuroscience, 2021)
Background: How ‘success’ is defined in clinical trials of deep brain stimulation (DBS) for refractory psychiatric conditions has come into question. Standard quantitative psychopathology measures are unable to capture all changes experienced by patients and may not reflect subjective beliefs about the benefit derived. The decision to undergo DBS for treatment-resistant depression is often made in the context of high desperation and hopelessness that can challenge the informed consent process. Partners and family can observe important changes in DBS patients and play a key role in the recovery process. Their perspectives, however, have not been investigated in research to-date. The aim of this study was to qualitatively examine patient and caregivers’ understanding of DBS for treatment-resistant depression, their expectations of life with DBS, and how these compare with actual experiences and outcomes. Methods: A prospective qualitative design was adopted. Semi-structured interviews were conducted with participants (six patients, five caregivers) before DBS-implantation and 9-months after stimulation initiation. All patients were enrolled in a clinical trial of DBS of the bed nucleus of the stria terminalis. Interviews were thematically analysed with data saturation achieved at both timepoints. Results: Two primary themes identified were: 1) anticipated versus actual outcomes, and 2) trial decision-making and knowledge. The decision to undergo DBS was driven by the intolerability of life with severe depression coupled with the exhaustion of all available treatment options. Participants had greater awareness of surgical risks compared with stimulation-related risks. With DBS, patients described cognitive, emotional, behavioural and physical experiences associated with the stimulation, some of which were unexpected. Participants felt life with DBS was like “a roller coaster ride” – with positive, yet unsustained, mood states experienced. Many were surprised by the lengthy process of establishing optimum stimulation settings and felt the intervention was a “work in progress”. Conclusions: These findings support existing recommendations for iterative informed consent procedures in clinical trials involving long-term implantation of neurotechnology. These rich and descriptive findings hold value for researchers, clinicians, and individuals and families considering DBS. Narrative accounts capture patient and family needs and should routinely be collected to guide patient-centred approaches to DBS interventions.